Transformative Effect of Li Salt for Proactively Mitigating Interfacial Side Reactions in Sodium-Ion Batteries - Jooeun Byun; Joon Ha Chang; Chihyun Hwang; Chae Rim Lee; Miseung Kim; Jun Ho Song; Boseong Heo; Sunghun Choi; Jong Hyeok Han; Hee-Jae Jeon; Beom Tak Na; Youngjin Kim; et al. (Nano-Micro Letters)
Highlights LiPF6 integration into sodium-ion battery electrolytes strengthens solid electrolyte interphase (SEI) film and stabilizes O3 electrode surfaces, enhancing cycleability with 92.7% at 400 cycles. Li-based SEI exhibits reduced solubility, effectively suppressing sodium-ion and electron leakage, and mitigating electrolyte decomposition on hard carbon electrode. The formation of Li-ion pillars on O3-type electrode surfaces significantly reduces oxygen release and electrolyte degradation, resulting in improved capacity retention.